New particle formation in China: Current knowledge and further directions - Wang, Z. B.; ZJ Wu; Yue, D. L.; Shang, D. J.; Guo, S.; Sun, J. Y.; Ding, A. J.; L. Wang; JK Jiang; H. Guo; Gao, J.; Cheung, H. C.; et al. (Science of the Total Environment, 2017)
New particle formation (NPF) studies have been conducted in China since 2004. Formation of new atmospheric aerosol particles has been observed to take place in diverse environments, even under the circumstances of high pre-existing particle loading, challenging the traditional and present understanding of the physicochemical nucleation mechanisms, which have been proposed based on the investigations in clean environments and under laboratory experimental conditions. This paper summarizes the present status and gaps in understanding NPF in China and discusses the main directions opening for future research. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: air ion spectrometer; atmospheric; cloud; condensation nuclei; environment; Environmental Sciences & Ecology; formation events; ionization mass-spectrometry; new particle formation; nucleation; Nucleation mechanism; nucleation mode particles; number size distributions; particle growth; Polluted; sorpes station; sulfuric-acid concentration; yangtze-river delta